(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Hyperhomocysteinemia is an important biological marker for adverse outcome of pregnancy. Objective: The aim of the present study was to see the association of high serum homocysteine with preeclampsia (PE). Methodology: This cross sectional study was carried out in the Department of Obstetrics and Gynaecology at Sir Salimullah Medical College & Mitford Hospital, Dhaka. All pregnant women with or without eclampsia admitted at the hospital were included in this study. Pregnant women with diabetes mellitus, chronic hypertension, multiple pregnancies, chronic renal disease and patients taking anti-folate drugs were excluded from this study. Fasting serum total homocysteine (tHomocysteine) concentration was estimated by Fluorescence Polarization Immunoassay (FPIA) method. Result: A total number of 50 PE patient [Severe PE (23) & Mild PE (27)] and 50 pregnant women without PE were selected purposively. Fasting serum total homocysteine (tHomocysteine) concentration was estimated by fluorescence polarization immunoassay (FPIA) method. Mean serum homocysteine concentration in severe PE, mild PE and pregnant women without PE were 11.5 4.58 mol/L, 10.43 5.12 and 5.70 1.30 respectively. Serum homocysteine was significantly increased in severe PE and mild PE in comparison to without PE group . Howere severe PE and mild PE group cases did not differ with respect to serum homocysteine. Conclusion: Significant positive correlation was found between serum homocysteine concentration and urinary total protein, uric acid level, systolic blood pressure and diastolic blood pressure. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16200 J Shaheed Suhrawardy Med Coll, 2013;5(1):21-25